Genetic characterization and population structure of Canela-Preta creole chicken - Carvalho, Débora Araújo de; Bonafe, Cristina Moreira; Rodriguez-Rodriguez, Maria Del Pilar; Almeida, Marcos Jacob de Oliveira; Sarmento, José Lindenberg Rocha; Britto, Fabio Barros; Silva, Martinho de Almeida e (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to genetically characterize and evaluate the population structure of Canela-Preta creole chicken of three breeding stocks belonging to the municipalities of Teresina, Oeiras and Queimada Nova, in the state of Piauí, Brazil. Twelve microsatellite markers and DNA samples from 118 chickens were used. After DNA extraction, the microsatellite markers were amplified by polymerase chain reaction (PCR). Statistical analyses of the observed and expected heterozygosity estimates, analysis of molecular variance, principal components analysis, Wright’s F-statistics, and analysis of population structure based on Bayesian analysis were performed. The analyses of genetic differentiation (using Amova) suggested low differentiation between the evaluated nucleuses, indicating this group as genetically unique. The results of the F-statistics indicated endogamy trend of the breeding stocks studied. Scatter plot and Bayesian analysis, used to show the structure of Canela-Preta birds, suggested the existence of four genetic groups and revealed that there is gene flow between the breeding stocks analysed. The evaluated microsatellite molecular markers showed to be polymorphic, which shows high variation in the samples and reveals their effectiveness in the study of characterization. The results indicate that Canela-Preta chickens are genetically structured.